2016
DOI: 10.1177/0363546516673836
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Hip Anchor Insertion From the Midanterior and Distal Anterolateral Portals With a Straight Drill Guide: A Cadaveric Study

Abstract: Caution should be employed when inserting anchors for labral refixation, particularly in anterior and medial locations (2-4 o'clock), as articular surface and psoas tunnel perforation may occur at a rate higher than previously anticipated. Portal selection does not appear to influence these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 22 publications
4
25
2
Order By: Relevance
“…When comparing anchor drilling from varying portal locations (anterior, anterolateral, and DALA), Dumont et al 1 found subchondral perforation rates of 21% from the anterior portal, 17% from the anterolateral portal, and 0% from the DALA portal. This is in contrast to our study (Degen et al 2 ), which found no significant difference in articular surface perforation rates when comparing anchors drilled from the midanterior (MA) portal with anchors drilled from the distal anterolateral portal. When evaluating outer cortex perforation rates when drilling from the anterior, anterolateral, and DALA portals, Dumont et al found perforation rates of 36%, 1%, and 8%, respectively.…”
Section: See Related Article On Page 2349contrasting
confidence: 99%
See 3 more Smart Citations
“…When comparing anchor drilling from varying portal locations (anterior, anterolateral, and DALA), Dumont et al 1 found subchondral perforation rates of 21% from the anterior portal, 17% from the anterolateral portal, and 0% from the DALA portal. This is in contrast to our study (Degen et al 2 ), which found no significant difference in articular surface perforation rates when comparing anchors drilled from the midanterior (MA) portal with anchors drilled from the distal anterolateral portal. When evaluating outer cortex perforation rates when drilling from the anterior, anterolateral, and DALA portals, Dumont et al found perforation rates of 36%, 1%, and 8%, respectively.…”
Section: See Related Article On Page 2349contrasting
confidence: 99%
“…To this end, we perform most of our anchor insertions from the DALA portal and switch to an MA portal drilling technique with a curved guide when 3-and 4-o'clock anchor holes perforate in a subchondral manner or through the outer cortex. Again, we believe the conclusion of Dumont et al that the DALA portal is safer is more consistent with our clinical experience, and our results (Degen et al 2 ) may have been under-reported owing to cartilage in our cadaveric model. Their anterior portal may be more proximal than our MA portal, which explains the greater rate of subchondral perforation.…”
Section: See Related Article On Page 2349supporting
confidence: 91%
See 2 more Smart Citations
“…To avoid this complication, it is recommended to drill the tunnels from the anterolateral and the distal anterolateral portals. 48 If rim trimming is necessary to resect the anterior acetabular wall and roof, meticulous preoperative planning is recommended to avoid excessive resection. Care must be taken in protrusio hips with a negative acetabular index and a large fossa, where removal of peripheral joint lunate surface can dramatically increase the transarticular contact forces, 25 increasing the risk of degeneration.…”
Section: Surgical Techniquementioning
confidence: 99%